Evaluation of permanent deformation of asphalt rubber using multiple stress creep recovery tests and flow number tests - Klinsky, Luis Miguel Gutierrez; Bardini, Vivian Silveira dos Santos; De Faria, Valeria Cristina (Transportes, 2020)
This study used the Multiple Stress Creep Recovery Test (MSCR) and the Flow number test to analyze the characteristics of asphalt rubber and its use in hot mix asphalt (HMA) regarding to their ability to withstand permanent deformation. MSCR tests were done in three commercial asphalt rubber and in the traditional asphalt binder 50/70. Flow number tests were performed in twenty four specimens of asphalt rubber mixtures and eight specimens of conventional asphalt mixtures. The results of these tests showed that all the asphalt rubber samples had lower compliance values (Jnr) in the MSCR test, which denotes that these modified binders improved the rutting resistance of HMA. This behavior was confirmed with flow number results, since the HMA produced with asphalt rubber had always higher flow number values, when compared to the conventional asphalt mixtures. The analysis of the data showed excellent correlation between Jnr values and FN values.